2000
DOI: 10.1007/bf02375557
|View full text |Cite
|
Sign up to set email alerts
|

Mg2Si and MSi2 (M=Ca, Fe) silicon alloys as possible anodes for lithium batteries

Abstract: Abstract. Several silicon alloys MgzSi and MSi2 (M = Ca, Fe) in powder tbrm have been tested as possible anodes in two electrode cells. These alloys react with lithium to form Li-Si alloys as detected by the X-ray diffraction. However, the initial uptake of lithium is poorer than expected, corresponding to 690, 250 and 100 mAh/g for the Mg, Ca and Fe systems, respectively. All the electrodes exhibit a drastic capacity fade upon cycling. X-Rays diffraction analysis correlated to the galvanostatic tests indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 9 publications
(11 reference statements)
0
16
0
Order By: Relevance
“…This gives rise to mechanical stresses that lead to cracks and eventual disintegration of the electrode and a failure of the battery [5]. Intermetallic compounds, such as silicides M-Si (with M: Mg [6][7][8], Mn [2,9], Mo [10], Fe [9,11], Ni [12], Nb, Ta, V, Ca, Cr [13,14], and Ti) [1] were first reported by Anani and Huggins as anode materials for Liion batteries [14], especially Mg 2 Si [6] and CrSi 2 [14]. Since, more work have been performed on silicon and silicon-metal alloys; on this regard, two interesting reviews have recently been published on the subject by Park et al [15] and Larcher et al [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gives rise to mechanical stresses that lead to cracks and eventual disintegration of the electrode and a failure of the battery [5]. Intermetallic compounds, such as silicides M-Si (with M: Mg [6][7][8], Mn [2,9], Mo [10], Fe [9,11], Ni [12], Nb, Ta, V, Ca, Cr [13,14], and Ti) [1] were first reported by Anani and Huggins as anode materials for Liion batteries [14], especially Mg 2 Si [6] and CrSi 2 [14]. Since, more work have been performed on silicon and silicon-metal alloys; on this regard, two interesting reviews have recently been published on the subject by Park et al [15] and Larcher et al [2].…”
Section: Introductionmentioning
confidence: 99%
“…Mg 2 Si has an anti-fluorine structure that was shown to accommodate Li-insertion according to the following path: Mg 2 Si + 2Li + 2e → Li 2 MgSi + Mg, followed by reaction of Mg with lithium to form an MgLi alloy [14,16]. However, other groups reported the following reaction pathway [7,8]: Mg 2 Si + 3Li + 3e → 2MgLi + SiLi. Initial capacities are typically usually high but the reversible capacity is quite low.…”
Section: Introductionmentioning
confidence: 99%
“…1) [1]. In recent years, it has attracted an increasing amount of interest for a wide range of applications in various fields, such as thermoelectrics and optics and in lithium-ion batteries, largely due to its low toxicity, unique optical and electrical properties, low costs of production, and environmental compatibility [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Pena et.al [7] have shown that Mg 2 Si delivers a much lower yet quite high initial capacity of about 690 mAh/g. Unfortunately, this value rapidly decreases down to 30 mAh/g already after 25 cycles.…”
Section: Introductionmentioning
confidence: 99%